Do We Really Not Know What Toulmin’s Analytic Arguments Are? - Kollárik, Tomáš (Informal Logic, 2023)
The aim of this paper is to challenge the idea that Toulmin’s main focus in The Uses of Argument is to critique formal deductive logic. I first try to challenge the argument that, on the basis of what Toulmin says about analytic arguments, it is impossible to determine exactly what they are. I will then attempt to determine the basic contours of analytic arguments. Finally, I will conclude that the concept of an analytic argument involves epistemological assumptions to which formal logicians are in no way committed by the nature of their discipline.